# Use the zero product property to find the solutions to the equation x^{2} – x – 6 = 0.

An equation in the form of ax^{2} + bx + c = 0 is a quadratic equation. It has a degree of two. The value of a ≠ 0.

## Answer: The solutions for the equation x^{2} – x – 6 = 0 using zero product property is x = 3 and x = - 2.

Let's find the solution.

**Explanation:**

The standard form of quadratic equation is x^{2} – x – 6 = 0 .

By using factorization of quadratic equation for the equation x^{2} - x – 6 = 0 and splitting the middle term we get, x^{2} - x – 6 = 0

⇒ x^{2 }+ 2x - 3x - 6 = 0

⇒ x (x + 2) - 3 (x + 2) = 0

⇒ (x - 3) (x + 2) = 0

Now, we use the zero product property.

We can have two cases:

⇒ x - 3 = 0 or,

⇒ x + 2 = 0

Hence, we have two solutions: x = 3 and x = - 2.

You can use Quadratic Equation Calculator to find the roots of a quadratic equation.